Pharmacoeconomic evaluation of first-line combination therapy with immunotherapy drugs and platinum-containing chemotherapy in adult patients with metastatic non-squamous non-small cell lung cancer - S. К. Zyryanov; I. N. Dyakov (Фармакоэкономика)
Objective: to evaluate the pharmacoeconomic efficacy of “atezolizumab + bevacizumab + paclitaxel + carboplatin” drug combination compared to “pembrolizumab + pemetrexed + carboplatin” combination in adult patients with non-small cell lung cancer (NSCLC) in the first line of therapy.Material and methods. The modeling was applied for cost minimization analyzis of using compared therapy regimens with comparable efficacy, and to estimate the impact on the healthcare budget when increasing the proportion of patients in the target population receiving “atezolizumab + bevacizumab + paclitaxel + carboplatin” combination. Published adjusted indirect comparison data were used in modeling. The calculations were based on the registered prices according to the state register of maximum selling prices.Results. The use of “atezolizumab + bevacizumab + paclitaxel + carboplatin” combination instead of “pembrolizumab + pemetrexed + carboplatin” combination will decrease the direct medical costs of therapy per 1 patient for 2 years by 28,165.00 rubles (–0.4%). The budget impact analysis showed that an increase in the proportion of patients receiving “atezolizumab + bevacizumab + paclitaxel + carboplatin” combination from 50% (current therapy practice) to 100% (considered therapy practice) will reduce the budget load for the population of 6,240 patients over 2 years by 256.1 million rubles (–0.64%).Conclusion. The results of pharmacoeconomic analysis demonstrated that the use of “atezolizumab + bevacizumab + paclitaxel + carboplatin” combination in first-line therapy for metastatic NSCLC is economically feasible and reduces the load on the budget compared to “pembrolizu- mab + pemetrexed + carboplatin” scheme.